Comb-shaped piezoelectric beam configuration for wideband vibration based energy scavenging: Analytical and simulation results - Diyana, N. H.; Abdul Muthalif, Asan Gani (2013)
For years, people have been harvesting energy from solar panels, wind turbines, hydroelectric generators and many more. These macro scale energy harvesting technologies have successfully grown in meeting the world’s energy demand. However, to operate low powered electronic devices; especially when being placed in a remote area; micro scale energy scavenging comes into the light. The most promising method is via vibration energy scavenging which converts mechanical energy (from vibration) to electrical energy by the effect of coupling between mechanical variables and electric or magnetic fields. In this paper, the focus is on unimorph piezoelectric energy harvesting. Mathematical modelling based on Euler- Bernoulli beam theory is derived as well. Simulations are done in MATLAB and COMSOL Multiphysics softwares. Finally, the optimal shape and configuration are presented in this paper as well as the study on the influence of tip mass on the output voltage.